Safety, pharmacokinetics and pharmacodynamics of single doses of rivaroxaban – an oral, direct factor Xa inhibitor – in elderly Chinese subjects - Jiang, Ji; Hu, Yufang; Zhang, Jianyan; Yang, Jueling; Mueck, Wolfgang; Kubitza, Dagmar; Bauer, Richard J.; Meng, Ling; Hu, Pei (Thrombosis and Haemostasis, 2010)
Rivaroxaban is a novel, oral, direct factor Xa (FXa) inhibitor for the prevention and treatment of thromboembolic disorders. The aim of this study was to investigate the safety, pharmacokinetics (PK) and pharmacodynamics (PD) of rivaroxaban in healthy, elderly Chinese subjects. In this single-centre, single-blind, placebo-controlled, parallel-group, dose-escalation study, 79 subjects, aged 59–74 years (mean 62.8), were randomised to receive once-daily oral doses of rivaroxaban 5, 10, 20, 30 or 40 mg. Rivaroxaban was well tolerated: there was a low incidence of treatment-emergent adverse events and all events were of mild intensity. Rivaroxaban was absorbed rapidly, reaching maximum plasma concentrations within 2–4 hours. The PK of rivaroxaban were dose dependent over the dose range tested. Maximal inhibition of FXa occurred 2–3 hours after dosing and returned to baseline after 24–48 hours, reflecting rivaroxaban plasma concentrations. Inhibition of FXa was associated with dose-dependent effects on global clotting tests. There were no clinically relevant differences in rivaroxaban plasma concentrations between male and female subjects. In conclusion, rivaroxaban was well tolerated and was found to have predictable PK and PD in healthy, elderly Chinese subjects.
Keywords: Chinese subjects; factor Xa inhibitor; oral anticoagulant; rivaroxaban